Enhanced Detection of Community-Acquired Pneumonia Pathogens With the BioFire® Pneumonia FilmArray® Panel - Gilbert, David N. (Diagn Microbiol Infect Dis, 2021)
BACKGROUND: Although most observational studies identify viral or bacterial pathogens in 50% or less of patients hospitalized with community-acquired pneumonia (CAP), we previously demonstrated that a multi-test bundle (MTB) detected a potential pathogen in 73% of patients. This study compares detection rates for potential pathogens with the MTB versus the Biofire® Pneumonia FilmArray® panel (BPFA) multiplex PCR platform and presents an approach for integrating BPFA results as a foundation for subsequent antibiotic stewardship (AS) activities. METHODS: Between January 2017 to March 2018, all patients admitted for CAP were enrolled. Patients were considered evaluable if all elements of the MTB and the BPFA were completed, and they met other a priori inclusion criteria. The primary endpoint was the percentage of potential pathogens detected using the MTB (8 viral and 6 bacterial targets) versus the BPFA (8 viral and 18 bacterial targets). Blood and sputum cultures were performed on all patients. Two or more procalcitonin (PCT) levels assisted clinical assessments as to whether detected bacteria were invading or colonizing. RESULTS: Of 585 enrolled patients, 274 were evaluable. A potential viral pathogen was detected in 40.5% with MTB versus 60.9% of patients with BPFA with an odds ratio (95% CI) of 9.00 (4.12 to 23.30) p<0.01. A potential bacterial pathogen was identified in 66.4% with the MTB vs 75.5% with the BPFA odds ratio (95% CI) of 2.09 (1.24 to 3.59), p 0.003). Low PCT levels helped identify detected bacteria as colonizers.